Effect of Application of Performance Assessment System Based on E-Performance and Competency on Work Achievement of Structural Employees Through Job Satisfaction as Intervening Variable (Study on Bondowoso Regency Government) - Angga Wahyudi, I Putu; Herlambang, Toni; Putu Martini, Ni Nyoman (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2022)
This research is motivated by several gaps or differences in research results with expert opinions, also supported by data on research problems, namely based on the results of employee performance evaluations in 2020 which were less than optimal, where the realization of performance achievements did not reach 90 at the end of the fiscal year. Evaluation data for filling out the E-application Performance shows that as many as 38% or about 900 employees do not fill in e-Kinerja to 100%. So the phenomenon of this research is the lack of effectiveness of employee performance in increasing competence, especially in the use of IT-based e-performance. The purpose of this study was to determine directly or indirectly the effect of evaluating performance based on the e-Kinerja application and employee competence on employee job performance through job satisfaction as an intervening variable on Structural Employees of the Bondowoso Regency Government. The total population of this study was 2,405 employees, while the number of samples was 168 using purposive sampling technique. The analysis technique used is the Structural Equation Model (SEM) using WarpPLS 5.0. The results of data analysis show that e-performance based performance appraisal and employee competence have a significant effect on job satisfaction, (2) e-performance based performance appraisal and employee competence and job satisfaction have a significant effect on employee performance, (2) e-performance based evaluation.